Zinc Stannate Nanocrystal–Based Ultrarapid‐Response UV Photodetectors. Issue 6 (26th April 2018) - Dong, Yuhang; Wang, Shalong; Zou, Yousheng; Liu, Shuting; Zhu, Zhengfeng; Li, Jvbing; Ju, Dan; Chen, Jun; Zhang, Kan; Liu, Xuhai; Zeng, Haibo
Abstract: Ternary‐oxide nanostructures are the most investigated as promising candidates for ultraviolet (UV) photodetectors (PDs) due to composition tunable bandgap and better photoconductivity. However, the assembled film–based UV PDs generally exhibit poor response speed because the internal defects of nanostructures and the discontinuity of assembled film obstruct transport of charges. Herein, a single‐crystal Zn2 SnO4 (ZTO) nanocrystal (NC)–assembled film UV photodetector is reported, improving the response speed several tens of times (τrise ≈ 0.2 ms, τdecay ≈ 0.43 ms). The I light /I dark ratio of the UV PD is over 10 3 . The ZTO NCs, with the bandgap of 3.9 eV, are prepared by laser ablation in liquid combined with hydrothermal reaction. The combination and dissociation of Zn–Sn–O ternary oxide are investigated to guarantee that single‐crystal ZTO NCs have high purity, clean surface, high specific surface area. Moreover, the NC‐assembled film is highly compact and continuous, which outperforms the conventional 1D nanostructures. This work provides a reliable novel approach to greatly improve the performances of UV PDs. Abstract : Single‐crystal Zn2 SnO4 nanoparticles are prepared via laser ablation in liquid combined hydrothermal synthesis. The single‐crystal Zn2 SnO4 nanocrystal–assembled film was constructed by a simple acentric‐deposition method. The devices showed both excellent photoresponse speed (τrise ≈ 0.2 ms, τdecay ≈ 0.42 ms) and I light / I dark ratio (over 10 3 ). This work provided a reliable novel manner to greatly improve the performances of ultraviolet photodetectors.